Situating architectural performance: 'star architecture' and its roles in repositioning the cities of Graz, Lucerne and Wolfsburg. Issue 9 (2nd September 2018) - Alaily-Mattar, Nadia; Bartmanski, Dominik; Dreher, Johannes; Koch, Michael; Löw, Martina; Pape, Timothy; Thierstein, Alain
ABSTRACT: Since the opening of the Guggenheim Museum in Bilbao in 1997, the topic of how 'star architecture' plays a decisive role in urban regeneration has been discussed in academic debates as well as in the media. Efforts to emulate the so-called Bilbao effect followed internationally. However, not every city that commissions the design of a public cultural building to a star architect seeks to replicate that effect. This overarching narrative has nevertheless constituted a powerful background representation. This paper discusses the supposed replicability of the 'effect'. The aim is to emphasize relational situatedness and plurality of roles of star architecture as a device of urban regeneration. The process of repositioning of a city does not necessarily follow the logic of international economic competition. When it comes to medium-sized cities, we observe that they aim at distinction within a specific field, in their nation-state, or try to reinvent their internal dynamics. This process can have expressive and symbolic, not merely instrumental character, and be understood as more of a socio-cultural performance rather than a purely economic investment. We juxtapose three empirical cases to illustrate the argument: Kunsthaus in Graz, Culture and Congress Centre Lucerne and Phaeno Science Centre in Wolfsburg.